A new approach to early diagnosis of congestive heart failure disease by using Hilbert–Huang transform. (December 2016) - Altan, Gokhan; Kutlu, Yakup; Allahverdi, Novruz
Highlights: Diagnosis of congestive heart failure (CHF) is achieved with a high accuracy rate and sensitivity rate than other works on the same databases. The most important feature that makes the study superior to other studies is the diagnosis of coronary artery disease (CAD) that is known as the early diagnosis of CHF with a high rate of accuracy and sensitivity. This work provides integration of two diagnostic systems into a single system. Abstract: Congestive heart failure (CHF) is a degree of cardiac disease occurring as a result of the heart's inability to pump enough blood for the human body. In recent studies, coronary artery disease (CAD) is accepted as the most important cause of CHF. This study focuses on the diagnosis of both the CHF and the CAD. The Hilbert–Huang transform (HHT), which is effective on non-linear and non-stationary signals, is used to extract the features from R-R intervals obtained from the raw electrocardiogram data. The statistical features are extracted from instinct mode functions that are obtained applying the HHT to R-R intervals. Classification performance is examined with extracted statistical features using a multilayer perceptron neural network. The designed model classified the CHF, the CAD patients and a normal control group with rates of 97.83%, 93.79% and 100%, accuracy, specificity and sensitivity, respectively. Also, early diagnosis of the CHF was performed by interpretation of the CAD with a classification accuracy rate of 97.53%, specificity of 98.18% and sensitivity of 97.13%. As a result, a single system having the ability of both diagnosis and early diagnosis of CHF is performed by integrating the CAD diagnosis method to the CHF diagnosis method.